2011
DOI: 10.1155/2011/725472
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Clinical Outcome after Laparoscopic Antireflux Surgery in Clinical Practice: Still a Controversial Issue

Abstract: Background. Laparoscopic antireflux surgery has shown to be effective in controlling gastroesophageal reflux (GERD). Yet, a universally accepted definition and evaluation for treatment success/failure in GERD is still controversial. The purpose of this paper is to assess if and how the outcome variables used in the different studies could possibly lead to an homogeneous appraisal of the limits and indications of LARS. Methods. We analyzed papers focusing on the efficacy and outcome of LARS and published in Eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 49 publications
0
5
1
Order By: Relevance
“…Postoperative outcome measurements are also not always objective and consistent; therefore, determining the success of surgery is sometimes difficult, and few studies have been performed. 25 Although our results demonstrate a high prevalence of pepsin-positive samples, we were unable to identify any specific clinical factors that may predict which patients are more likely to have silent aspiration events. In the absence of any specific factors, pepsin testing of BAL fluid samples-which seems to have a high positive predictive value-may be a feasible means to identify these patients.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Postoperative outcome measurements are also not always objective and consistent; therefore, determining the success of surgery is sometimes difficult, and few studies have been performed. 25 Although our results demonstrate a high prevalence of pepsin-positive samples, we were unable to identify any specific clinical factors that may predict which patients are more likely to have silent aspiration events. In the absence of any specific factors, pepsin testing of BAL fluid samples-which seems to have a high positive predictive value-may be a feasible means to identify these patients.…”
Section: Discussioncontrasting
confidence: 55%
“…24 Postoperative outcome measurements are also not always objective and consistent, therefore determining the success of surgery sometimes difficult. 25 …”
Section: Discussionmentioning
confidence: 99%
“…One third of patients, submitted to fundoplication, is reported to take acid-lowering compounds (mostly PPIs) after ARS, but only few studies have specified whether drug use was on a regular or occasional basis [76]. A meta-analysis of randomized controlled trials (RCTs) [77] found that – after ARS – 14 % of patients still require antisecretory drugs.…”
Section: Resultsmentioning
confidence: 99%
“…Although medication use is often considered as an outcome measure for successful ARS, some studies have shown that antisecretory drug use does not correlate with true recurrent reflux in most patients [76] and does not necessarily indicate a failure of the procedure. A significant proportion of patients taking medications after operation are using them to relieve non-reflux symptoms and only one third of patients displays an abnormal esophageal exposure to acid after surgery [76].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation